Customer Satisfaction with BSI Mobile: A Review of Features, User Experience, and Security Among the People of Palembang City - Adelia Ramadhanti; M. Rasyid Redho Pratama; Dian Horid (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2025)
Advancements in technology have spurred innovation within the banking industry, particularly through the digitalization of services such as BSI Mobile. This research aims to analyze the influence of product features, user experience, and security on customer satisfaction at Bank Syariah Indonesia KC Palembang Sudirman. The study employs a quantitative approach, utilizing IBM SPSS 23 for statistical analysis. Primary data were collected through questionnaires distributed to 100 respondents, all of whom are users of the BSI Mobile application at the aforementioned branch. The analytical techniques applied include tests of validity and reliability, classical assumption testing, multiple linear regression analysis, and hypothesis testing using the t-test, F-test, and coefficient of determination (R²). The findings reveal that the product feature variable does not significantly influence customer satisfaction. However, both user experience and security variables have a positive and significant impact on satisfaction levels. Furthermore, when examined collectively, the three variables, product features, user experience, and security, simultaneously influence customer satisfaction in using BSI Mobile at Bank Syariah Indonesia KC Palembang Sudirman.